2001
DOI: 10.2486/indhealth.39.175
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Effect of Silicon Carbide Whisker to the Rat Lung.

Abstract: Abstract:We studied the short-term effect of silicon carbide whisker (SiCW) in vivo by instillation and inhalation to the rat lung. SiCW was instilled low dose (2 mg/0.5 ml saline) or high dose (10 mg/ 0.5 ml) intratracheally into the lungs of 25 rats. SiCW was also inhaled to another 25 rats at the average concentration of 10.4 mg/m 3 for 1 month. In instillation study, the lung had focal alveolitis with the destruction of alveolar wall especially at 3 days after the instillation, and the lesion remained as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In the previous paper 8) , we showed that the biological half times were almost the same (1.5-4 months) when the lung burden was lower than 0.65 mg. The relationship between the biological half time and the amount of fibers deposited in rat lungs in this experiment coincided with those in the previous experiments obtained by using glass fiber, aluminum-silicate ceramic fiber and potassium titanate whisker, but we reported in the previous paper that SiCW may have a minor histopathological effect on rat lung in the six months 3) . At this stage, the effects of the amount deposited and the biological half time on the histopathological change are not yet clear.…”
Section: Clearance Of the Deposited Sicw In The Rat Lungssupporting
confidence: 92%
“…In the previous paper 8) , we showed that the biological half times were almost the same (1.5-4 months) when the lung burden was lower than 0.65 mg. The relationship between the biological half time and the amount of fibers deposited in rat lungs in this experiment coincided with those in the previous experiments obtained by using glass fiber, aluminum-silicate ceramic fiber and potassium titanate whisker, but we reported in the previous paper that SiCW may have a minor histopathological effect on rat lung in the six months 3) . At this stage, the effects of the amount deposited and the biological half time on the histopathological change are not yet clear.…”
Section: Clearance Of the Deposited Sicw In The Rat Lungssupporting
confidence: 92%
“…The results were then categorized into four grades and the score was determined. (Ogami et al, 2001).…”
Section: Morphological Proceduresmentioning
confidence: 95%
“…In our previous study we reported that both inflammation and fibrosis were non-progressive in a SiCW intratracheal-instillation rat model 14) . It has been reported that surfactant has the ability to reduce dynamic surface tension 6,7) .…”
Section: Discussionmentioning
confidence: 99%